The newest COI molecular detection of Asian redtail catfish Hemibagrus nemurus (Valenciennes, 1840) in Progo River, Magelang, Central Java, Indonesia (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This study describes the newest deoxyribonucleic acid (DNA) barcoding Asian redtail catfish (Hemibagrus nemurus) in the Progo River, Magelang, Central Java, Indonesia. Materials and Methods: Ten fish were caught in the Progo River, Magelang, Central Java, Indonesia. The polymerase chain reaction was the molecular diagnosis to detect the sequences of DNA of Cytochrome Oxidase I compared to National Center for Biotechnology Information data (GenBank). Results: The results showed that the percent identity was not 100% with H. nemurus data from other locations (GenBank), including Indonesia. The closest percent identity was H. nemurus from Java Island (Accession ID: MK312566.1) with 97.6% similarity. The genetic mutation that happened might be due to environmental change (pollution) in the Progo River recently. Conclusions: This study showed a genetic mutation in H. nemurus from Progo River may be caused by environmental change. Low pollution exposure levels may not be detrimental (lethal) to fish. However, it can affect fish fertility, which leads to population degradation (gene variation). Attention must be increased for fish survival in the future.J. Adv. Vet. Anim. Res., 9(4): 591–600, December 2022http://doi.org/10.5455/javar.2022.i628